(untitled) (Biological Sciences - PJSIR, 2022)
Green forage yield, dry matter yield and forage quality of oat variety S-81 as affected by different cutting treatments were determined during 1987-1989 at the National Agricultural Research Centre, Islamabad. Green forage yield, dry matter yield and crude fibre increased, while seed yield and crude protein declined with maturity. Maximum green forage and dry matter yields with considerably inferior forage quality as determined by lower crude protein and higher crude fibre values were recorded at the 50% flowering stage. Minimum green forage and dry matter yields with superior qua- lity forage were recorded in the crop harvested at 70 and 85 days after planting. The results of this research indicate that it is possible to have a satisfactory forage and grain crop from oat which were harvested once for forage at 115 days after planting.